A Proposed Solution for the Chicken-Egg Dilemma in Pricing Currency Options - Ariful Hoque; Chandrasekhar Krishnamurti (Australasian Accounting, Business and Finance Journal, 2013)
The implied volatility (IV) estimation process suffers from an obvious chicken-egg dilemma: obtaining an unbiased IV requires the options to be priced correctly and calculating an accurate option price (OP) requires an unbiased IV. We address this critical issue in two steps. First, the Granger causality test is employed, which confirms the chicken-and-egg problem in the IV computing process. Secondly, the concept of “moneyness volatility (MV)” is introduced as an alternative to IV. MV is modelled based on an option’s moneyness (OM) during the life of the option’s contract. The F-test, Granger-Newbold test and Diebold-Mariano test results consistently show that MV outperforms IV in estimating the exchange rate volatility for pricing options. Further, these series of tests across six major currency options substantiate the validity as well as the reliability of the results. We posit that MV offers a unique solution for pricing currency options accurately.
Keywords: Currency options pricing; implied volatility; moneyness volatility; Granger causality test; Granger-Newbold